Role of pyroptosis in hemostasis activation in sepsis - Zhu, Chengrui; Liang, Yingjian; Luo, Yangtuo; Ma, Xiaochun (Frontiers in Immunology, 2023)
Sepsis is frequently associated with hemostasis activation and thrombus formation, and systematic hemostatic changes are associated with a higher risk of mortality. The key events underlying hemostasis activation during sepsis are the strong activation of innate immune pathways and the excessive inflammatory response triggered by invading pathogens. Pyroptosis is a proinflammatory form of programmed cell death, that defends against pathogens during sepsis. However, excessive pyroptosis can lead to a dysregulation of host immune responses and organ dysfunction. Recently, pyroptosis has been demonstrated to play a prominent role in hemostasis activation in sepsis. Several studies have demonstrated that pyroptosis participates in the release and coagulation activity of tissue factors. In addition, pyroptosis activates leukocytes, endothelial cells, platelets, which cooperate with the coagulation cascade, leading to hemostasis activation in sepsis. This review article attempts to interpret the molecular and cellular mechanisms of the hemostatic imbalance induced by pyroptosis during sepsis and discusses potential therapeutic strategies.